Healthcare utilization and cost burden of Huntington's disease among Medicare beneficiaries in the United States. (1st January 2021) - Exuzides, Alex; Reddy, Sheila R.; Chang, Eunice; Ta, Jamie T.; Patel, Anisha M.; Paydar, Caleb; Yohrling, George J.
Abstract: Aims: To examine healthcare utilization and costs in a US Medicare population diagnosed with Huntington's disease (HD). Methods: This was a retrospective matched cohort study using Medicare fee-for-service (FFS) claims data using 2013–2017 Research Identifiable Files. Medicare beneficiaries diagnosed with HD based on the presence of at least one medical claim with an International Classification of Diseases, Ninth or Tenth Revision, Clinical Modification (ICD-9/10-CM) diagnosis code for HD (ICD-9-CM: 333.4; ICD-10-CM: G10) during the identification period (2014–2016). Beneficiaries without HD were drawn from a 5% random sample of Medicare beneficiaries and 1:1 matched to those with HD for comparison. All-cause and HD-related (any utilization related to HD diagnosis or symptoms associated with HD) healthcare utilization and costs were reported. Results: We identified 3, 688 matched pairs of beneficiaries with and without HD. Of those with HD, 1, 922 (52.1%) were late-stage, 916 (24.8%) were middle-stage, and 850 (23.1%) were early-stage. Mean [SD] annual total healthcare costs were higher for HD beneficiaries than beneficiaries without HD ($41, 631 [57, 393] vs. $17, 222 [31, 218], p  < .001) and were primarily driven by outpatient pharmacy costs ($19, 182 [45, 469] vs. $4, 318 [11, 553], p  < .001). In the stratified analysis, total healthcare costs were highest among beneficiaries with late-stage HD (mean [SD] cost: $20, 475 [$41, 122] for early-stage vs. $29, 733 [$44, 977] for middle-stage vs. $56, 657 [$64, 185] for late-stage; p  < .001). Limitations: Results are not generalizable to beneficiaries enrolled in other non-FFS Medicare plans. Administrative claims are intended for billing purposes, not research, and may not capture all symptoms, comorbidities, and other adverse events. Conclusions: This original, comprehensive analysis of healthcare utilization and economic burden among Medicare beneficiaries with HD found that healthcare needs and associated costs are substantially higher among Medicare beneficiaries who are diagnosed with HD compared to beneficiaries without HD.